Population of Natural Enemies in Three Varieties of Rice Plants in Turikale Subdistrict, Maros District - Nining Triani Thamrin; Aksal Mursalat (Agrotech Journal, 2020)
Rice (Oryza sativa L.) is an annual crop that plays an important role in meeting the food sources of the Indonesian population. In addition, rice plants have a diversity of insects as their natural enemy. This study aims to determine the population of natural enemies of 3 rice varieties, namely Inpari 30, Ciliwung, and Mekongga varieties. The research location is the rice fields in Turikale Subdistrict, Maros District. The method used for the study was the survey location of rice fields with each paddy field size of about 20 x 15 m. The results showed that there were 3 types of predators namely Lycosa, Coccinella, and Orthetrum which were found in each variety with varied total numbers at every 2-week observation interval. The highest population of Lycosa was found in the Inpari 30 (6 wap) variety, the highest Coccinella population also was found in the Inpari 30 (10 wap) variety, while the highest Orthetrum population was found in the Mekongga variety (6 wap). The highest proportion of each variety was Lycosidae 50% in the Inpari 30 variety, Lycosidae 51.35% in the Ciliwung variety, and Lycosidae 44.44% in the Mekongga variety